Determinants of predation success: How to survive an attack from a rattlesnake. (27th March 2019) - Whitford, Malachi D.; Freymiller, Grace A.; Higham, Timothy E.; Clark, Rulon W.
Abstract: The selection pressures that arise from capturing prey and avoiding predators are some of the strongest biotic forces shaping animal form and function. Examining how performance (i.e., athletic ability) affects the outcomes of encounters between free‐ranging predators and prey is essential for understanding the determinants of predation success rates and broad scale predator–prey dynamics, but quantifying these encounters in natural situations is logistically challenging. The goal of our study was to examine how various metrics of predator/prey performance determine predation success by studying natural predator–prey interactions in the field with minimal manipulation of the study subjects. We used high‐speed video recordings of free‐ranging sidewinder rattlesnakes (predator, Crotalus cerastes ) and desert kangaroo rats (prey, Dipodomys deserti ) to study how performance at various stages of their encounters alters the outcome of their interactions. We found that predation success depends on (a) whether the rattlesnake struck accurately, (b) if the rattlesnake strike was accurate, the reaction time and escape manoeuvres of the kangaroo rat, and (c) if the kangaroo rat was bitten, the ability of the kangaroo rat to use defensive manoeuvres to avoid subjugation by the snake. The results of our study suggest that the role of performance in predator–prey interactions is complex, and the determinants of predation success are altered by both predator and prey at multiple stages of an interaction in ways that may not be apparent in many experimental contexts. A plain language summary is available for this article. Abstract : Plain Language Summary